2019
DOI: 10.1111/eci.13073
|View full text |Cite
|
Sign up to set email alerts
|

Decreased glucocorticoid receptor expression during critical illness

Abstract: Introduction In critically ill patients, the hypothalamic‐pituitary‐adrenal axis is activated, resulting in increased serum cortisol concentrations. However, in some patients, especially those with sepsis, cortisol levels are relatively low for the degree of illness severity. Therefore, in the present project, we aim to characterize the time course of glucocorticoid receptor (GCR) alpha and beta expression in peripheral polymorphonuclear cells of critically ill septic or nonseptic patients using real‐time PCR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 53 publications
(94 reference statements)
1
17
0
1
Order By: Relevance
“…Moreover, we observed a more signi cant decrease in the MFI of GR expression in Treg cells and CD3 + CD4 + T lymphocytes but none in the percentage of GR expression. Previous studies have found decreased expression of GRs in peripheral polymorphonuclear cells in critically ill patients [22], and antagonism to GRs aggravates viral and bacterial infections [30]. The results of this study suggest that the decrease in intracellular GR expression in patients who experienced CA may be one of the causes of GC resistance, due to insu cient binding of GRs and GCs, GC insensitivity, and the inability of GCs to effectively exert anti-in ammatory and immunosuppressive effects.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Moreover, we observed a more signi cant decrease in the MFI of GR expression in Treg cells and CD3 + CD4 + T lymphocytes but none in the percentage of GR expression. Previous studies have found decreased expression of GRs in peripheral polymorphonuclear cells in critically ill patients [22], and antagonism to GRs aggravates viral and bacterial infections [30]. The results of this study suggest that the decrease in intracellular GR expression in patients who experienced CA may be one of the causes of GC resistance, due to insu cient binding of GRs and GCs, GC insensitivity, and the inability of GCs to effectively exert anti-in ammatory and immunosuppressive effects.…”
Section: Discussionsupporting
confidence: 48%
“…The a nity of GRs to GC in circulating monocytes is decreased in patients with acquired immunode ciency syndrome [21]. The expression of GR is decreased in critical illness [22], pediatric septic shock, and patients with high serum cortisol [23]. However, hitherto, no study has reported on the GR expression after ROSC in patients who experienced CA.…”
Section: Introductionmentioning
confidence: 99%
“…GRβ homodimers can interact with glucocorticoid response elements (GRE) in the DNA, however their binding does not activate transcription (69). Generally, GRβ is expressed at very low levels compared to GRα; however, its expression is increased in inflammatory diseases, including critical illness, and this might be associated with decreased sensitivity to GCs and CIRCI (79).…”
Section: Glucocorticoid Receptor-alphamentioning
confidence: 99%
“…Clinical studies, including autopsies, in patients with severe sepsis and septic shock have reported a significant reduction in GRα expression in circulating cells (79,(134)(135)(136)(137); heart (125), liver and skeletal muscle (125,138), and a significant increase in GRβ expression in the heart and liver (125). GRα mRNA in neutrophils correlates negatively with plasma IL-6 levels and shows gradual recovery overtime in survivors (135).…”
Section: Glucocorticoid Receptor Alpha In Critical Illnessmentioning
confidence: 99%
“…Finally, our group was able to demonstrate that critically-ill steroid-free patients have a highly variable expression of both GCR isoforms in peripheral polymorphonuclear cells. Moreover, GCR expression and HPA axis function undergo a biphasic response during acute or subacute critical illness; this dissociation of reduced GCR expression and elevated cortisol might imply an abnormal stress response[ 42 , 43 ].…”
Section: Gcrmentioning
confidence: 99%